Immune-mediated enterocolitis is associated with immune checkpoint inhibitors: A pharmacovigilance study from the FDA Adverse Event Reporting System (FAERS) database - Connor Frey (PLoS ONE, 2025)
Purpose Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment by demonstrating significant efficacy across multiple malignancies. However, by interfering with immune regulatory pathways, they can lead to immune-related adverse events (irAEs), including immune-mediated enterocolitis. This study aimed to evaluate the real-world risk of immune-mediated enterocolitis across different ICIs using data from the FDA’s Adverse Event Reporting System (FAERS). Methods A disproportionality analysis was conducted using FAERS data to assess the association between different ICIs and the risk of immune-mediated enterocolitis. The risk was analyzed across three ICI classes: cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) inhibitors, programmed death-1 (PD-1) inhibitors, and programmed death-ligand 1 (PD-L1) inhibitors. Results The analysis revealed significant variability in the risk of immune-mediated enterocolitis among ICIs. CTLA-4 inhibitors, particularly tremelimumab and ipilimumab, exhibited the strongest association with enterocolitis. Among PD-1 inhibitors, nivolumab demonstrated the highest risk, while PD-L1 inhibitors, including durvalumab and atezolizumab, had a lower but still notable association. Conclusions These findings underscore the need for vigilant monitoring and early intervention in patients receiving ICIs. The differential risk profile among ICIs suggests that physicians should consider enterocolitis risk when selecting and managing immunotherapy regimens.